Use-wear patterns on wild macaque stone tools reveal their behavioural history - Haslam, M; Gumert, M; Biro, D; Carvalho, S; Malaivijitnond, S (Public Library of Science, 2013)
Burmese long-tailed macaques (Macaca fascicularis aurea) are one of a limited number of wild animal species to use stone tools, with their tool use focused on pounding shelled marine invertebrates foraged from intertidal habitats. These monkeys exhibit two main styles of tool use: axe hammering of oysters, and pound hammering of unattached encased foods. In this study, we examined macroscopic use-wear patterns on a sample of 60 wild macaque stone tools from Piak Nam Yai Island, Thailand, that had been collected following behavioural observation, in order to (i) quantify the wear patterns in terms of the types and distribution of use-damage on the stones, and (ii) develop a Use-Action Index (UAI) to differentiate axe hammers from pound hammers by wear patterns alone. We used the intensity of crushing damage on differing surface zones of the stones, as well as stone weight, to produce a UAI that had 92% concordance when compared to how the stones had been used by macaques, as observed independently prior to collection. Our study is the first to demonstrate that quantitative archaeological use-wear techniques can accurately reconstruct the behavioural histories of non-human primate stone tools.